2010
DOI: 10.1103/physrevb.81.075401
|View full text |Cite
|
Sign up to set email alerts
|

Controlled electron doping into metallic atomic wires:Si(111)4×1-In

Abstract: We demonstrate the controllable electron doping into metallic atomic wires, indium wires self-assembled on the Si͑111͒ surface, which feature one-dimensional ͑1D͒ band structure and temperature-driven metal-insulator transition. The electron filling of 1D metallic bands is systematically increased by alkali-metal adsorption, which, in turn, tunes the macroscopic property, that is, suppresses the metal-insulator transition. On the other hand, the dopant atoms induce a local lattice distortion without a band-gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 38 publications
5
53
1
1
Order By: Relevance
“…This underlines a notable interwire coupling, which should also be reflected by the conductivity components measured at room temperature. Moreover, its transition temperature can be tuned or even quenched by various adsorbates [11,12]. In this study, we restrict ourselves to the adsorption of oxygen, which chemisorbs dissociatively at room temperature on In/Si(111) [13], in agreement with theory [14].…”
Section: Introductionmentioning
confidence: 95%
“…This underlines a notable interwire coupling, which should also be reflected by the conductivity components measured at room temperature. Moreover, its transition temperature can be tuned or even quenched by various adsorbates [11,12]. In this study, we restrict ourselves to the adsorption of oxygen, which chemisorbs dissociatively at room temperature on In/Si(111) [13], in agreement with theory [14].…”
Section: Introductionmentioning
confidence: 95%
“…Global characteristics such as the transition temperature (T c ) and transport property of this In/Si(111)-4×1 surface have been reported to be affected significantly by small amounts of defects [13,[20][21][22][23][24][25][26][27][28]. In a recent series of diffraction experiments, the defects created by depositing metal atoms (In and Na) or by exposing the surface to gases (hydrogen and oxygen) were found to change the transition temperature [23][24][25]27].…”
Section: Introductionmentioning
confidence: 96%
“…Various adsorbates like In, Na, and H were reported to reduce the transition temperature (T c ) of the 4 × 1-8 × 2 phase transition, locally destabilizing the 8 × 2 phase. [12][13][14][15] In contrast, an early study on Na adsorbates reported the increase of T c up to room temperature (RT). 16 Although the defects themselves were not characterized, the condensation of the 8 × 2 phase by native defects was also observed.…”
Section: Introductionmentioning
confidence: 98%
“…3,17 However, a later scanning tunneling microscopy (STM) study showed that the local Na-induced phase is clearly different from the low temperature 8 × 2 CDW state and the CDW T c itself is suppressed significantly. 15 At a high Na coverage, the Na-induced local perturbations and the ordering of Na adsorbates themselves dominate. 15 A Na adsorbate at a low coverage was shown to donate electrons into the 1D metallic state and the reduced T c could largely be understood by the deviation from the optimal doping.…”
Section: Introductionmentioning
confidence: 99%